Report cards: Parental preferences, information and school choice in Haiti - Michael Bogner; Gregory Elacqua; Isabel Jacas; Christopher Neilson; Anne Sofie Westh Olsen (Inter-American Development Bank (IDB), 2023)
This paper studies school choice and information in the context of education markets in rural Haiti. Using a market level randomized control trial, we evaluate the aggregate effect of providing test score information on subsequent test scores, prices, and enrollment. After the intervention, we find that private schools have higher test scores, with an average increase of 0.3 standard deviations in treated markets. However, we are unable to detect significant changes to prices and market shares. These findings suggest that providing information in poor education markets can improve market efficiency and benefit children's welfare.
Keywords: I20; I21; I22; I24; I25; I28; 330; private schooling; information asymmetries; school choice; economic development; Haiti